Against Exclusionary Gaelic Language Policy: A Response to Ó Giollagáin and Caimbeul. Issue 1 (February 2022) - McLeod, Wilson; Dunbar, Robert; Macleod, Michelle; O'Rourke, Bernadette; Dunmore, Stuart; Armstrong, Timothy Currie
Abstract : This article considers a range of weaknesses and deficiencies in the article 'Moving Beyond Asocial Minority-Language Policy' by Conchúr Ó Giollagáin and Iain Caimbeul and the underlying research study on which it was based. The authors' presentation of previous research was inadequate and the framing of their survey results was sensationalistic, risking the demoralisation of Gaelic speakers and the weakening of social or political support for the language. The authors fail to justify and properly define the key terms used in their analysis, including 'vernacular community' and 'Gaelic group', so that there is a pervasive lack of clarity to their discussion, with serious implications for their key policy proposal. We also identify shortcomings in the geographic framing of their study; which areas were included and which were not. We then challenge the social classification they use in their analysis, and their rigid distinction between Gaelic speakers in their study area and all those living elsewhere. We then demonstrate how the authors' presentation of current Gaelic policy is incomplete, misleading and biased, and we critique their proposals for fundamental changes to the current policy structure, including the creation of a new Gaelic community trust. We argue that strengthening existing policy structures and exploiting such structures much more energetically and effectively offers a better approach to strengthening the language, both in the areas studied and elsewhere in the country.